Resurrection of Cremanthodium gracillimum and C. wardii (Asteraceae, Senecioneae), with notes on the genus in Myanmar - Wang, Long (Phytotaxa, 2020)
Cremanthodium gracillimum and C. wardii (Asteraceae, Senecioneae), two species endemic to northern Myanmar, have been previously reduced to the synonymy of C. rhodocephalum and C. campanulatum, respectively. Critical morphological comparison, however, indicates that both of them are separate species easily distinguishable in the genus. The specific status of the two species is therefore reinstated herein. A full description is given for the two species, and some taxonomic notes are made on other Cremanthodium species from Myanmar. A key to all the species of the genus in this country is provided.